ANALISIS PRODUKSI DAN PENDAPATAN RUMPUT LAUT DI DESA BULAGI DUA KECAMATAN BULAGI KABUPATEN BANGGAI KEPULAUAN - Donny Osmond Aluman; Hadayani Hadayani; Effendy Effendy (Agroland: Jurnal Ilmu-ilmu Pertanian, 2016)
This study aims were to: (1) determine the effect of the length of rope stretch, seeds, labor, harvesting time and farming experience on the production of seaweed in Bulagi Dua village Bulagi subdistrict of Banggai Kepulauan district, and (2) determine the income of the seaweed farming in Bulagi Dua village Bulagi sub district of Banggai Kepulauan district. The research used a survey method and sampling was done randomly. The number of samples in this study was 44 families. The results showed that: (1) the length of rope stretch (land area), the number of seeds, labor, and time of harvestingpartially had significant effect whereas the farming experience was not significant on the seaweeds production in Bulagi Dua village Bulagi subdistrict of Banggai Kepulauan district (2) the total revenue earned by the respondents was IDR 10,994,739.36/0.55 ha/planting season equal to IDR 19,710,174.88/ha/planting season. Keywords:  Revenues and Seaweed Production.